Omnidirectional and heat-resistant infrared reflector and method for manufacturing the same
By forming multiple lattice periods in 3D photonic crystals, combining 3D printing technology and preceramic resin processing, the problem of manufacturing 3D photonic crystals and the problem of high temperature and durability in the prior art is solved, and the complete infrared light is achieved Directional reflection and high temperature stability.
Patent Information
- Application Number
- CN202080082081.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-11
- Filing Date
- 2020-08-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-08-12
AI Technical Summary
The prior art is difficult to manufacture 3D photonic crystals with complete photonic bandgap, especially in the infrared spectral range, and traditional reflectors are not durable in high temperature environments and cannot reflect photons from all directions.
Using a three-dimensional photonic crystal structure, which contains rods of materials with different refractive indices, it is manufactured by forming multiple lattice cycles in three-dimensional space and is manufactured by 3D printing technology, combining photopolymerization and heat treatment of preceramic resins to generate high-temperature and stable ceramics. Material to achieve omnidirectional infrared reflection.
It realizes omnidirectional reflection in the infrared spectral range and maintains stability in high temperature environments, and is suitable for high temperature applications such as thermal insulation coatings and thermal management systems.
Smart Images

Figure CN114746784B_ABST
Abstract
Description
[0001] Priority data
[0002] This international patent application claims priority to U.S. Provisional Patent Application No. 62 / 940,294 filed on November 26, 2019 and U.S. Patent Application No. 16 / 990,096 filed on August 11, 2020, each of which is hereby incorporated by reference herein. Field of the Invention
[0003] The present invention generally relates to structures that can reflect infrared light from all incident directions. Background of the Invention
[0005] Photonic crystals contain periodic lattices with different dielectric structures (i.e., different refractive indices). Light that interacts with the periodic lattice is redistributed into allowed directions and blocked in forbidden directions. The forbidden directions are the "photonic band gap" of the photonic crystal. Photonic crystals can be designed with photonic band gaps that prevent light of specific wavelengths and directions from propagating within the photonic crystal. Photonic crystals use subwavelength structures to create photonic band gaps. The structure does not support light with frequencies within the band gap, and such light is reflected away when incident on the material.
[0006] A great deal of research has been devoted to photonic crystals in the infrared and visible spectrum. In a one-dimensional (1D) photonic crystal, layers with different dielectric constants can be deposited or adhered together to form a band gap in a single direction. Prior art reflectors are Bragg stacks with varying refractive indices and thicknesses tuned in one dimension. Bragg reflectors reflect infrared light most efficiently at normal incidence and are less effective for larger angles of incidence. 1D photonic crystals cannot have a complete band gap.
[0007] Two-dimensional (2D) photonic crystals are periodic in two dimensions and uniform in the third dimension. 2D photonic crystals are generally easier to manufacture than 3D photonic crystals. For example, holes can be drilled in a substrate that is transparent in two dimensions to the radiation wavelengths that the band gap is designed to block. 2D photonic crystals cannot have a complete band gap. Although 2D photonic crystal waveguides are useful for certain applications such as planar circuits and distributed feedback lasers, there are many applications that require 3D photonic crystals.
[0008] Three-dimensional (3D) photonic crystals have a varying refractive index in three dimensions and are therefore able to be perfect reflectors, regardless of the angle of incidence, thereby providing the structure with a "complete photonic band gap". Certain crystal lattices can form 3D photonic crystals with complete or incomplete band gaps, depending on the lattice parameters. If a photonic crystal does not allow light within a certain wavelength range to propagate for all polarizations and directions (omnidirectional), the photonic crystal has a complete photonic band gap for this range of light wavelengths. Regardless of the angle of incidence, the light is not propagated but reflected. There are many types of lattice unit cells. Due to this geometric state in which the spatial period of the rhombus lattice is almost independent of the spatial direction, the rhombus unit cell has desirable properties.
[0009] A necessary condition for a complete photonic bandgap is that the dielectric lattice is periodic in all three dimensions. However, forming 3D photonic crystals has proven difficult so far. This is especially true when the desired bandgap wavelength is in the infrared spectrum, because the dimensions of the unit cell are generally smaller than the bandgap wavelength.
[0010] The work of making 3D photonic crystals with a predetermined structure is very arduous. Yablonovitch et al., "Photonic band structure: the face centered-cubic case employing nonspherical atoms", Phys. Rev. Lett. [Physical Review Letters] Vol. 67, No. 17, 2295-2298 (1991) describes the formation of artificial 3D photonic crystals by repeatedly drilling an array of intersecting millimeter-sized holes in a dielectric material. Such photonic crystals have band gaps in the microwave (non-infrared) range of the spectrum and are of limited practical significance.
[0011] Several complex techniques have been developed to fabricate 3D photonic crystals, including forming individual dielectric layers, stacking and bonding these layers, and forming 3D waveguides to construct the crystals. Other techniques involve self-assembling microspheres or materials deposited on a printing template, and then depositing a high-refractive-index material atop the structure. Mechanically complex crystal modifications have been used to fabricate rhombus or rhombus-like unit cells, which require micro-drilling along six axes in the material, which is impractical.
[0012] 3D photonic crystals have many applications, including miniaturized optical and electro-optical integrated circuits and devices. IR reflectors, which are traditionally configured in 1D or 2D, can also benefit from 3D photonic crystals. IR reflectors are one example.
[0013] If 3D photonic crystals are made from high temperature ceramic materials, they can withstand extreme thermal environments. There are several applications that require reflectors that can withstand high temperatures, work within a broadband spectrum, and reflect light incident from all directions. Control of IR reflection or emission is used in thermal management, blackbody emission feature control, and thermophotovoltaic devices. Infrared optical reflectors are useful for reflecting heat for automobiles and aircraft.
[0014] Bragg reflectors, in addition to not being omnidirectional, are generally not resistant to high temperatures. In a paper by Shen et al., Optics Express, Vol. 287 (2001), entitled "Temperature dependence of reflectivity of absorbing Bragg reflectors," the authors demonstrate that in some absorption bands the reflectivity decreases with increasing temperature. Furthermore, most dielectric materials used for Bragg stacks cannot withstand temperatures above 1000°C. Finally, Bragg stacks exhibit sensitivity to the angle of incidence. At large angles, the bandwidth of the reflected light decreases and the wavelength also changes. These characteristics are problematic for reflectors that are inside an engine that is exposed to high temperatures and must reflect radiation from all angles.
[0015] A combination of omnidirectional reflectivity and temperature stability is required for applications such as thermal barrier coatings. The efficiency of jet propulsion engines decreases as heat is lost through the walls. Thermal barrier coatings are used to insulate the heat in the engine from the highly thermally conductive metal walls (which would remove the heat). However, the gases in the combustion chamber radiate 0.1-1 MW / m 2 of power, and much of this energy is absorbed by the coating material. Therefore, a reflector is needed that can withstand temperatures above 1000°C and can reflect peak blackbody radiation at a wavelength of, for example, about 2-3 μm. SUMMARY OF THE INVENTION
[0017] The present invention addresses the above-identified needs in the art, as will now be summarized and then further described in detail below.
[0018] Some variations provide an omnidirectional infrared reflector comprising a three-dimensional photonic crystal comprising:
[0019] rods of a first material having a first refractive index, wherein the rods are arranged to form a plurality of lattice periods in three dimensions, wherein the rods are connected at a plurality of nodes, wherein the lattice period is characterized by a lattice spacing, and wherein the rods are characterized by a rod radius or width; and
[0020] a second material having a second refractive index, the second refractive index being lower than the first refractive index, wherein the rods are embedded in the second material,
[0021] The lattice spacing and the rod radius or width are selected to produce a photonic band gap within a selected band of the infrared spectrum.
[0022] The photonic bandgap may be a complete photonic bandgap within the selected band of the infrared spectrum.In some embodiments, the selected band of the infrared spectrum has a wavelength from about 1 μm to about 15 μm, such as from about 2 μm to about 3 μm.
[0023] In some embodiments, the lattice spacing is from about 0.5 μm to about 20 μm, such as from about 1 μm to about 3 μm.
[0024] In some embodiments, the rod radius or width is from about 50 nm to about 5 μm.The ratio of the rod radius or width to the lattice spacing can be selected, for example, from about 0.05 to about 0.50.
[0025] A plurality of lattice periods is at least 2 lattice periods and typically at least 4 lattice periods in all dimensions. In one or more dimensions, for example, there may be at least 5, 10, 20, 50, 100 or more lattice periods.
[0026] In some embodiments, the three-dimensional photonic crystal has a rhombus-shaped unit cell. In other embodiments, the three-dimensional photonic crystal has a wood-pile-shaped unit cell.
[0027] In some embodiments, the first refractive index is at least 2, and the second refractive index is less than the first refractive index.
[0028] The first material can be a ceramic material, such as, but not limited to, a ceramic material selected from the group consisting of SiC, SiOC, Si3N4, SiCN, TiO2, ZrO2, ZnO, and combinations thereof. In some embodiments, the ceramic material is a pyrolyzed form of a pre-ceramic resin, which is optionally a 3D printed pre-ceramic resin, as discussed in detail later in this specification.
[0029] The second material may be selected from the group consisting of MgF2, LiF, CaF2, BaF2, SiO2, SiOC and combinations thereof. In some typical embodiments, the second material is air.
[0030] In some embodiments, at least some of the nodes are structural nodes configured to mechanically enhance the rods. In a particular embodiment, all of the nodes are structural nodes configured to mechanically enhance the rods. The geometric shape of the structural nodes can be, for example, spherical, ellipsoidal, or irregular. The structural nodes have a structural node radius or width that is at least 10% greater than the rod radius or width, such as at least 25%, 50%, or 100% greater than the rod radius or width. The structural node material can be made of the same material as the first material or of a different material. In some embodiments, the structural node material is selected from the group consisting of SiC, SiOC, Si3N4, SiCN, TiO2, ZrO2, ZnO, and combinations thereof. The structural node material optionally has a refractive index within 10% of the refractive index of the first material.
[0031] In some embodiments, the omnidirectional infrared reflector is thermally stable when exposed to a temperature of 1300° C. in an air atmosphere at a pressure of 1 bar for 24 hours.
[0032] In some embodiments, the omnidirectional infrared reflector includes multiple layers, each layer having a different three-dimensional photonic crystal.
[0033] Other variations provide a method for making a three-dimensional photonic crystal, the method comprising:
[0034] (a) Selecting a three-dimensional photonic crystal unit cell;
[0035] (b) providing a pre-ceramic resin capable of photopolymerization when exposed to light having a wavelength of from about 200 nm to about 700 nm;
[0036] (c) 3D printing and photopolymerizing the pre-ceramic resin into a pre-ceramic polymer, wherein the pre-ceramic polymer is spatially arranged in the geometric shape of the three-dimensional photonic crystal unit cell; and
[0037] (d) thermally treating (eg, pyrolyzing) the pre-ceramic polymer at a temperature from 150° C. to about 1200° C. to convert the pre-ceramic polymer into a ceramic material, thereby producing a three-dimensional photonic crystal.
[0038] In some embodiments, step (d) is performed in an atmosphere containing argon, nitrogen, hydrogen, ethane, propane, ammonia, silane, or a combination thereof.
[0039] The method may further include, after step (d), high temperature treating the three-dimensional photonic crystal at a temperature from 1200° C. to about 1600° C. Optionally, the high temperature treatment is performed in an atmosphere containing argon, nitrogen, hydrogen, ethane, propane, ammonia, silane or a combination thereof.
[0040] In some methods, the pre-ceramic resin employed in step (b) contains at least one element selected from the group consisting of Si, C, N, Ti, Ge, Zr, and Zn.
[0041] In some methods, the three-dimensional photonic crystal produced in step (d) comprises:
[0042] rods of a ceramic material having a first refractive index, wherein the rods are arranged to form a plurality of lattice periods in three dimensions, wherein the rods are connected at a plurality of nodes, wherein the lattice period is characterized by a lattice spacing, and wherein the rods are characterized by a rod radius or width; and
[0043] a second material having a second refractive index, the second refractive index being lower than the first refractive index, wherein the rods are embedded in the second material,
[0044] The lattice spacing and the rod radius or width are selected to produce a photonic band gap within a selected band of the infrared spectrum. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Depicted is a 3D photonic crystal of a rhombus lattice in some embodiments of the invention.
[0046] Figure 2 A close-up view of a 3D photonic crystal depicting a rhombus lattice in some embodiments of the present invention.
[0047] Figure 3 is a bandgap plot of an exemplary rhombohedral lattice for different refractive indices (n) and dimensions (r / a).
[0048] Figure 4 Calculated reflection spectrum for an exemplary diamond lattice tuned to have a mid-gap wavelength of 2.5 μm as a function of the number of lattice periods along the propagation direction.
[0049] Figure 5A depicts a 3D photonic crystal of a woodpile lattice in some embodiments of the invention, Figure 5B yes Figure 5A A partial picture of .
[0050] Figure 6 is a graph of the band gap of a woodpile lattice for different dimensions and refractive indices in some embodiments of the present invention.
[0051] Figure 7 The fitted optical constants measured by ellipsometry of the 3D-printed carbosilane resin after heat treatment in Example 1 are shown (n=dashed line, k=solid line).
[0052] Figure 8is an SEM image showing a 4-cell thick 3D printed polycarbosilane woodpile structure in Example 2 (scale bar = 30 μm).
[0053] Fig. 9 is a SEM image of the woodpile-shaped SiOC ceramic material in Example 2 (scale bar = 30 μm).
[0054] Fig.10 is a high magnification SEM image of the SiOC woodpile structure (scale bar = 5 μm), showing the pillar width of about 0.5 μm and the pillar-pillar spacing of about 3 μm in Example 2 as well as the structural nodes. DETAILED DESCRIPTION
[0055] The present structures, systems, compositions and methods will now be described in detail with reference to various non-limiting examples.
[0056] This description will enable those skilled in the art to make and use the invention, and describes several embodiments, modifications, variations, alternatives and uses of the invention. These and other embodiments, features and advantages of the invention will become more apparent to those skilled in the art when reference is made to the following detailed description of the invention in conjunction with the accompanying drawings.
[0057] As used in this specification and the appended claims, the singular forms "a / an" and "the" include plural referents unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0058] Unless otherwise indicated, all numerical values expressing conditions, concentrations, dimensions, and the like used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary at least as a function of the particular analytical technique.
[0059] The term "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. "Comprising" is a specialized term used in claim language, meaning that the specified claim elements are essential, but other claim elements may be added and still constitute a concept within the scope of the claim.
[0060] As used herein, the phrase "consisting of excludes any elements, steps, or ingredients not specified in the claim. When the phrase "consisting of" (or variations thereof) appears in a clause in the body of a claim, rather than immediately following the preamble, the phrase is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole. As used herein, the phrase "consisting essentially of limits the scope of a claim to the specified elements or method steps, plus those that do not materially affect the basis and novel feature or features of the claimed subject matter.
[0061] With respect to the terms "comprising," "consisting of," and "consisting essentially of," when one of these three terms is used herein, the presently disclosed and claimed subject matter may include the use of either of the other two terms. Thus, in some embodiments not otherwise expressly recited, any instance of "comprising" may be replaced by "consisting of," or alternatively, "consisting essentially of."
[0062] Some variations of the invention provide structures that can reflect infrared light ("IR") from all incident directions. The structures can be produced by a process involving direct printing of high refractive index materials on a nanoscale or microscale in three dimensions. This 3D printing method allows for complex photonic crystal lattices, including (but not limited to) diamond lattices - thereby overcoming the conventional limitations of stacking successive layers and etching each layer to define the photonic crystal lattice. The printed material can be a pre-ceramic polymer that is subsequently converted to a high temperature ceramic material, thereby enabling applications that are not possible with standard IR reflectors.
[0063] Some variations provide an omnidirectional infrared reflector comprising a three-dimensional photonic crystal comprising:
[0064] rods of a first material having a first refractive index, wherein the rods are arranged to form a plurality of lattice periods in three dimensions, wherein the rods are connected at a plurality of nodes, wherein the lattice period is characterized by a lattice spacing (a), and wherein the rods are characterized by a rod radius or width; and
[0065] a second material having a second refractive index, the second refractive index being lower than the first refractive index, wherein the rods are embedded in the second material,
[0066] The lattice spacing and the rod radius or width are selected to produce a photonic band gap within a selected band of the infrared spectrum.
[0067] In this specification, "rods" function as pillars in a three-dimensional photonic crystal framework. These rods may have a circular cross section, an elliptical cross section, a rectangular cross section, a square cross section, a triangular cross section or other geometric shapes.
[0068] The photonic bandgap can be a complete photonic bandgap within a selected band of the infrared spectrum. In some embodiments, the selected band of the infrared spectrum is from about 1 μm to about 25 μm, such as from about 2 μm to about 3 μm, or from about 3 μm to about 10 μm, or from about 10 μm to about 25 μm. The photonic bandgap can be adjusted by selecting the lattice constant in the design of the three-dimensional photonic crystal.
[0069] In some embodiments, the lattice spacing a is from about 0.5 μm to about 20 μm, such as from about 1 μm to about 3 μm. In various embodiments, the lattice spacing a is, for example, about 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, or 25 μm. Typically, for a given structure, the lattice spacing is a single value, although there can be some deviation from the average.
[0070] In some embodiments, the rod radius or width is from about 50 nm to about 5 μm. In various embodiments, the rod radius or width is, for example, about 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, or 10 μm. When the rods have a circular cross-section (i.e., a cylindrical rod), the radius is the radius of the cylinder. When the rods have an elliptical cross-section, the width can be the short radius, the long radius, or the effective radius. When the rods have a square cross-section, the width is the length of the square side. When the rods have a rectangular cross-section, the width can be the rectangular width or the effective radius. For other geometries, the rod width is the effective radius (i.e., half the effective diameter). Typically, for a given structure, the rod radius or width is a single value, although there can be some deviation from the average. In some embodiments (e.g. Fig.10 ), these rods are substantially, but not completely, elliptical in their cross-section.
[0071] The ratio of rod radius or width to lattice spacing can be selected, for example, from about 0.05 to about 0.5, such as about 0.1, 0.2, 0.3, or 0.4.
[0072] A plurality of lattice periods is at least 2 lattice periods and typically at least 4 lattice periods in all dimensions. In one or more dimensions, for example, there may be at least 5, 10, 20, 50, 100 or more lattice periods.
[0073] In some embodiments, the three-dimensional photonic crystal has a "rhombus unit cell". The rhombus unit cell does not refer to the material of the photonic crystal being a rhombus (carbon allotrope), but rather to a unit cell in which the connections of the rods (pillars) approximate the bonding pattern in the atomic rhombus structure. The rhombus unit cell can be viewed as a pair of intersecting face-centered cubic lattices, each of which is separated in each dimension by one-quarter of the width of the unit cell. For an exemplary rhombus lattice structure containing multiple rhombus unit cells, see Figure 1 and 2 .
[0074] Men et al., “Robust topology optimization of three-dimensional photonic-crystal band-gap structures,” Opt. Express 22, 22632-22648 (2014), is incorporated herein by reference for its teachings of mimicking photonic band gaps in 3D crystalline geometries and demonstrating that rhombic lattices of pillars have optimal band gap sizes over a wide range of topologies and refractive indices.
[0075] In other embodiments, the three-dimensional photonic crystal has a "woodpile shaped unit cell" (also referred to as a "log pile unit cell"). There are multiple layers of rods in the woodpile unit cell, where one layer contains parallel rods and an adjacent layer contains perpendicular rods. Moreover, each set of adjacent layers has an offset of half a pitch in the lattice constant compared to the next set of adjacent layers above or below the first set of adjacent layers. That is, for a woodpile structure with four layers, the first and third layers are parallel to each other and offset by half a pitch; the second and fourth layers are parallel to each other and also offset by half a pitch; and the second and fourth layers are perpendicular to the first and third layers. For an exemplary woodpile structure containing multiple woodpile shaped unit cells, see Figure 5A and 5B The woodpile structure generally does not form a band gap as wide as the rhombohedral lattice structure.
[0076] The structure of the 3D photonic crystal is preferably based on a rhombus unit cell or a woodpile unit cell. However, the three-dimensional photonic crystal may have other unit cells, such as (but not limited to) Yablonovite unit cells, rhombus-like unit cells, woodpile-like unit cells with alternating adjacent layer groups offset at a spacing different from half a lattice gap, woodpile-like unit cells with adjacent layers not completely perpendicular or not completely parallel to each other, etc. Different types of interpenetrating unit cells can be used to form mixed unit cells. The method described below enables the manufacture of unit cells with essentially any selected geometry. It will also be understood that lattice defects may occur in one or more individual unit cells of the overall structure; the present invention does not require perfect unit cells.
[0077] In some embodiments, the first refractive index is at least 2 and the second refractive index is less than the first refractive index. For example, the first refractive index can be about, or at least about 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 4, 4.5, 5, 5.5, or 6. The second refractive index can be about, or at least about 2.5, 2.4, 2.3, 2.2, 2.1, 2, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, or 1 (and less than the first refractive index). These refractive indices can be average refractive indices within a selected band of the infrared spectrum.
[0078] The first material can be a ceramic material, such as (but not limited to) a ceramic material selected from the group consisting of SiC, SiOC, Si3N4, SiCN, TiO2, ZrO2, ZnO and combinations thereof. In some embodiments, the ceramic material is a pyrolyzed form of a pre-ceramic resin, which is optionally a 3D printed pre-ceramic resin.
[0079] In embodiments where a ceramic material selected from SiC or SiOC is provided, it will be appreciated that intermediate materials may be produced in which oxygen content is present but the oxygen content is less than 29 wt %, which is the stoichiometric mass content of oxygen in SiOC. Pure SiC has no oxygen. References to SiC and SiOC in the present disclosure will be understood to also include references to materials containing silicon, carbon and 0 to about 30 wt % oxygen, such as about 1, 2, 5, 10, 15, 20, 25, 28, 29 or 30 wt % oxygen. In materials containing SiOC, the overall oxygen content in the material may be greater than 30 wt %, such as (but not limited to) when SiO2 is present. Examples 1 and 2 herein give examples of ceramic SiC / SiOC materials containing various oxygen contents.
[0080] The second material may be, for example, selected from the group consisting of MgF2, LiF, CaF2, BaF2, SiO2, SiOC, and combinations thereof. In some typical embodiments, the second material is air, which has a refractive index of about 1. In certain embodiments, the second material is or includes SiOC that has been modified to have a refractive index from about 1.4 to about 1.9, such as via a reactive RF magnetron sputtering technique. In certain embodiments, the first material and the second material are both primarily SiOC, but one or both of these materials are modified such that the refractive index of the second SiOC material is less than the refractive index of the first SiOC material.
[0081] In some embodiments, at least some of the nodes are structural nodes configured to mechanically enhance the rods. In a particular embodiment, all of the nodes are structural nodes configured to mechanically enhance the rods. The geometric shape of the structural nodes can be, for example, spherical, ellipsoidal, or irregular. The structural nodes have a structural node radius or width that is at least 10% greater than the rod radius or width, such as at least 25%, 50%, or 100% greater than the rod radius or width. The structural node material can be made of the same material as the first material or of a different material. In some embodiments, the structural node material is selected from the group consisting of SiC, SiOC, Si3N4, SiCN, TiO2, ZrO2, ZnO, and combinations thereof. The structural node material optionally has a refractive index within 10% of the refractive index of the first material.
[0082] In some embodiments, the omnidirectional infrared reflector is thermally stable when exposed to a temperature of 1300° C. for 24 hours in an air atmosphere at a pressure of 1 bar. In various embodiments, the omnidirectional infrared reflector is thermally stable when exposed to a temperature of 1000° C., 1100° C., 1200° C., 1300° C., 1400° C., 1500° C., or 1600° C. for 24 hours in an air atmosphere at a pressure of 1 bar.
[0083] Photonic crystals as described herein preferably create a complete photonic band gap in which there are no photon states. Whether a particular 3D photonic crystal has a complete or incomplete photonic band gap depends on a particular lattice type and its parameters (e.g., size, shape, and spacing of rods). The band gap properties of a photonic crystal formed by a given lattice type (e.g., rhombus) can be calculated by solving Maxwell's equations for the propagation of electromagnetic waves in a periodic lattice. A technique for determining the band gap properties of a 3D photonic crystal based on lattice parameters is described in Ho et al. "Existence of a photonic gap in periodic dielectric structures", Phys. Rev. Lett. [Physical Review Letters], Vol. 65, No. 25, 3152-3155 (1990), which is incorporated herein by reference. Temperature effects can be taken into account in the calculation. If the structure is heated, the radiated blackbody spectrum will be changed by the density of states in the periodic lattice. It can be determined whether there is still no IR emission within the selected bandgap when the temperature is increased to the use temperature (such as 1000°C or higher). In some embodiments, a bandgap that is complete at room temperature remains complete at elevated temperatures, or is nearly complete at elevated temperatures, such as, for example, 500°C, 800°C, 1000°C, 1200°C, or 1500°C.
[0084] In some embodiments, the omnidirectional infrared reflector comprises a plurality of layers, each layer having a different three-dimensional photonic crystal. A plurality of layers refers to at least 2 and potentially 3, 4, 5, 6, 7, 8, 9, 10 or more layers. In some embodiments, the omnidirectional infrared reflector comprises a plurality of regions, each of which has a different three-dimensional photonic crystal (e.g., one region has a rhombus unit cell and another region has a woodpile unit cell).
[0085] The invention will now be described in some embodiments with reference to the accompanying drawings, which should not limit the invention in any way.
[0086] Figure 1 Depicted is a rhombus lattice of a 3D photonic crystal 100. The rhombus lattice is a preferred lattice structure because the rhombus unit cell produces a wider photonic band gap. The rhombus lattice is spread in all three dimensions with a lattice periodicity a to produce the 3D photonic crystal 100.
[0087] Figure 2 A close-up view of a 3D photonic crystal 200 depicting a rhombus lattice. Figure 2 2, cylindrical rods 210 (radius r) are connected at nodes 230. The lattice spacing 220 is labeled a. The rods 210 are embedded in a second material 240. The nodes 230 (radius>r) serve as structural connectors between the rods 210 to improve the strength of the structure 200.
[0088] Figure 3 yes Figure 1 Bandgap diagram of the structure for different refractive index (n) and dimension (r / a). Figure 1 (and Figure 2 ) is defined by two dimensions in the unit cell: the lattice constant a, and the radius r of the cylindrical rod. Due to the scaling invariance of Maxwell's equations, the optical properties are determined solely by the refractive index and the ratio r / a, which is determined along Figure 3 The x-axis varies with , while the y-axis represents the normalized frequency ωa / 2πc (ω = frequency, a = lattice constant, and c = speed of light). Figure 3 In the figure, the shaded area indicates that there is a complete photonic band gap for different values of n. For a fixed r / a, the band gap frequency can be tuned by adjusting a. Due to this scaling property, the appropriate measure for the size of the band gap is the ratio between the band gap width and the center frequency, which does not vary with the lattice constant. Assuming the medium is air (n=1.0003), a material with n=2.6 has a maximum band gap ratio of 15%. This means that if the center of the band gap is chosen to be 2μm wavelength, the gap covers 1.85μm to 2.15μm.
[0089] Figure 4is the calculated reflection spectrum of a rhombus lattice (connected rods) tuned to an intermediate band wavelength of 2.5 μm as a function of the number of lattice periods along the propagation direction. The SiC pillar material is assumed to be lossless (k=0) and the refractive index n=2.35. The geometric ratio r / a=0.13, where the lattice constant is set at a=1.68 μm to tune the intermediate state wavelength to 2.5 μm. In this curve, the number of lattice periods in the direction of light propagation varies from N=1 to N=5 (N is the number of unit cells), where the structure achieves near perfect reflection once N=4, corresponding to a total material thickness of less than 7 μm in this case.
[0090] Figure 5A A woodpile lattice 3D photonic crystal 500 is depicted. Figure 5A Local actions Figure 5B , showing that the woodpile unit cell consists of rods with width w and height h and lattice spacing a. Figure 5B In the embodiment, the rod (column) material 510 in one layer is perpendicular to the rod material 510' in the adjacent layer. The rods 510 / 510' are embedded in the second material 540. Figure 5B A half-pitch offset between adjacent layer groups is shown in .
[0091] Figure 6 Figure 2 is a bandgap plot of the woodpile lattice for different dimensions and refractive index. The height h of the rods is set to a constant h = 0.25a, while the width w of the rods is varied. The woodpile structure shows a smaller bandgap than the rhombus lattice structure. For a refractive index of n = 2.6, the bandgap is less than 8%, which is about half the bandgap of the rhombus lattice.
[0092] Some variations of the invention provide a method for making a three-dimensional photonic crystal, the method comprising:
[0093] (a) Selecting a three-dimensional photonic crystal unit cell;
[0094] (b) providing a UV-curable pre-ceramic resin, which is preferably capable of photopolymerization when exposed to light having a wavelength of from about 200 nm to about 700 nm;
[0095] (c) 3D printing and photopolymerizing the pre-ceramic resin into a pre-ceramic polymer, wherein the pre-ceramic polymer is spatially arranged in the geometric shape of the three-dimensional photonic crystal unit cell; and
[0096] (d) pyrolyzing the pre-ceramic polymer at a temperature from 150° C. to about 1200° C. to convert the pre-ceramic polymer into a ceramic material, thereby producing a three-dimensional photonic crystal.
[0097] In some methods, the three-dimensional photonic crystal produced in step (d) comprises:
[0098] rods of a ceramic material having a first refractive index, wherein the rods are arranged to form a plurality of lattice periods in three dimensions, wherein the rods are connected at a plurality of nodes, wherein the lattice period is characterized by a lattice spacing, and wherein the rods are characterized by a rod radius or width; and
[0099] a second material having a second refractive index, the second refractive index being lower than the first refractive index, wherein the rods are embedded in the second material,
[0100] The lattice spacing and the rod radius or width are selected to produce a photonic band gap within a selected band of the infrared spectrum.
[0101] In some embodiments, step (d) is performed in an atmosphere containing argon, nitrogen, hydrogen, ethane, propane, ammonia, silane, or a combination thereof.
[0102] The method may further include, after step (d), high temperature treating the three-dimensional photonic crystal at a temperature from 1200° C. to about 1600° C. Optionally, the high temperature treatment is performed in an atmosphere containing argon, nitrogen, hydrogen, ethane, propane, ammonia, silane or a combination thereof.
[0103] "Pre-ceramic" in this disclosure refers only to the ability to be ultimately converted into a ceramic material. It should be noted that the disclosed pre-ceramic resin formulations are precursors to pre-ceramic polymers, which themselves are precursors to ceramic materials. As contemplated herein, "resin" means a composition that can be polymerized or cured, further polymerized or cured, or cross-linked. Resins can include monomers, oligomers, prepolymers, or mixtures thereof.
[0104] It should be noted that in the present disclosure, all references to "UV," "UV curable," "UV curing based," etc. should include not only references to ultraviolet radiation, but also other electromagnetic radiation bands that may be effective for photopolymerization in various embodiments, including microwave radiation, terahertz radiation, infrared radiation, visible radiation (light), ultraviolet radiation, and X-rays.
[0105] In some methods, the UV-curable pre-ceramic resin employed in step (b) contains at least one element selected from the group consisting of Si, C, N, Ti, Ge, Zr, and Zn.
[0106] Pre-ceramic monomers such as siloxanes, silazanes, carbosilanes or combinations thereof can be converted into UV-curable pre-ceramic resins by adding UV-active functional groups such as vinyl, allyl, methacrylate, acrylate, epoxy and / or thiol groups. By using UV-curable pre-ceramic resins, structures can be written directly using, for example, stereolithography, two-photon lithography or multi-beam interference lithography. For example, advances in two-photon lithography allow 3D printing of UV-curable pre-ceramic resins with sub-micron resolution.
[0107] Eckel et al., “Additive manufacturing of polymer-derived ceramics,” Science, vol. 351, no. 6268, pp. 58-62 (January 1, 2016), and U.S. Patent Application Publication No. 2018 / 0148380A1 to Eckel et al., published on May 31, 2018, are each incorporated herein by reference for teaching exemplary UV-curable pre-ceramic resins that can be used in the present invention.
[0108] Various UV-curable pre-ceramic resins will now be further described. These UV-curable pre-ceramic resins can be used in step (b) of the above method. In certain embodiments, the disclosed UV-curable pre-ceramic resins can be provided as compositions for making 3D photonic crystals or potentially for making 2D or 1D photonic crystals.
[0109] In various embodiments, a UV-curable pre-ceramic resin for making three-dimensional photonic crystals includes a UV-curable pre-ceramic resin that provides a main ceramic framework when pyrolyzed. The UV-curable pre-ceramic resin may include one or more monomers, oligomers or polymers containing at least one Si-C, Si-N, Si-O or Si-S bond in some or all of the skeleton repeating units. The side chain groups of the molecules in the resin may be, for example, hydrogen, inorganic functional groups and / or organic functional groups. The organic or inorganic functional groups may be UV-active functional groups such as vinyl, allyl, methacrylate, acrylate, epoxy group and / or thiol group. In various embodiments, the side chain groups of the molecules in the resin are selected from the group consisting of: hydrogen, halide ions, substituted cyclic or non-cyclic hydrocarbon groups, unsubstituted cyclic or non-cyclic hydrocarbon groups, aromatic groups, groups containing unsaturated C=X double bonds, groups containing unsaturated C≡X triple bonds and combinations thereof, wherein X may be C, S, O or N. The UV-curable pre-ceramic resin may contain a combination of different unsaturated bonds. Among these various unsaturated bonds, a typical bond is a C=C double bond at the terminal position, wherein the three substitutions on the C=C bond are hydrogen atoms.
[0110] Specific examples of the pre-ceramic resin include polycarbosilane, polymethylcarbosilane; polyallylcarbosilane; allylhydropolycarbosilane; trivinylborazine; 2,4,6-trimethyl-2,4,6-trivinylcyclotrisilazane; 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasilazane; B,B'B"-triethynyl-N,N'N"-trimethylborazine; B,B'B"-triethynylborazine; 1,2,3,4,5,6-hexamethylcyclotrisilazane; 1,1,3,3,5,5-hexamethylcyclotrisilazane; 1,2-dimethylsilazane; 1,1-perhydrosilazane; 1,3-divinyl-1,3-diphenyl-1,3-dimethyldisilazane; 1,3-divinyl-1,1,3,3-tetramethyldisilazane Silazane; 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasilazane; 1,1,3,3,5,5,7,7-octamethylcyclotetrasilazane; or combinations or derivatives thereof. It is noted that any resin disclosed herein may be provided in monomeric, oligomeric or polymeric form. Specific examples of UV-active functional groups include 4-vinyl-1-cyclohexene-1,2-epoxide; 1,2-epoxy-5-hexene; 2-methyl-2-vinyl-oxetane; allyl methacrylate; allyl acrylate; vinyl acrylate; vinyl methacrylate; acrylic acid; methacrylic acid; allyl mercaptan; 3,4-epoxy-1-butene; vinyl; allyl; acrylate; methacrylate; or combinations or derivatives thereof.
[0111] The UV-curable pre-ceramic resin may be included in a UV-curable pre-ceramic formulation, which may include other components as described below.The UV-curable pre-ceramic formulation may contain from about 1 wt % to about 100 wt % of the UV-curable pre-ceramic resin.
[0112] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a catalyst. In some embodiments, the catalyst assists the crosslinking and / or polymerization of the UV-curable pre-ceramic resin. In some embodiments, the catalyst increases the rate of vinyl addition. The catalyst can be a homogeneous and / or heterogeneous catalyst. The catalyst can include a metal complex in the form of ML, wherein the metal M is selected from transition metals such as Pt, Pd, Ru, Rh, Ni and / or Co; and wherein the ligand L is selected from halides, alkyls, aryls, aliphatic unsaturated groups, carbon monoxide and / or organosilicon groups. The catalyst can be in the form of a metal salt. The catalyst can be in the form of metal particles supported on a catalyst carrier, such as silica, alumina, zeolite, carbon or a combination thereof. Specific examples of catalysts include Pt on silica; Pt on alumina; Pt on activated carbon; Pt on SBA-15 (mesoporous silica); Pt or Pd on MCM-41 (mesoporous silicate-aluminosilicate layered material); chloroplatinic acid hydrate (Speier catalyst); platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution (Karstedt catalyst); tris (triphenylphosphine)-rhodium (I) chloride; benzylidene bis (tricyclohexylphosphine) dichlororuthenium (II); dichloro (1,5-cyclooctadiene) platinum (II); or combinations thereof. When present, the catalyst is present in a concentration of from about 0.00001 wt % to about 5 wt % of the UV-curable pre-ceramic formulation.
[0113] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a photoinitiator that generates free radicals by intermolecular bond cleavage and / or intermolecular dehydrogenation when exposed to light having a wavelength from about 200 nm to about 700 nm, such as from about 200 nm to about 500 nm. Combinations of different types of photoinitiators can be used in the polymerization process, such as to provide different rates of reactions initiated by different photoinitiators, or to allow multi-wavelength curing. Specific examples of photoinitiators include 2,2-dimethoxy-2-phenylacetophenone; 2-hydroxy-2-methylpropiophenone; camphorquinone; bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; benzophenone; benzoyl peroxide; thioxanthone; or combinations or derivatives thereof. When present, the photoinitiator is present in a concentration of from about 0.00001 wt % to about 10 wt % of the UV-curable pre-ceramic formulation.
[0114] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a UV sensitizer. A UV sensitizer may be included in the formulation to allow the UV system to react with the long UV wavelength of a photoinitiator that typically absorbs at a short wavelength, thereby broadening the photoreactivity of the formulation. Typically, this is the case with cationic photoinitiators, which are limited to absorption in a narrow band such as about 355 nm. The UV sensitizer interacts with UV light, typically at a wavelength of 400 nm or higher, and then interacts with the photoinitiator to produce free radicals or acids. The UV sensitizer forms an excited triplet state when absorbing UV light; through electron or energy transfer, the UV sensitizer reacts with the photoinitiator to produce free radicals and / or Bronsted acids, thereby initiating photopolymerization. Specific examples of UV sensitizers include dibutoxyanthracene; diethoxyanthracene; 1-chloro-4-propoxythioxanthone; 2-isopropylthioxanthone; 4-isopropylthioxanthone; or combinations or derivatives thereof. When present, the UV sensitizer is present in a concentration of from about 0.00001 wt % to about 10 wt % of the UV curable pre-ceramic formulation. The molar ratio of UV sensitizer to photoinitiator may be, for example, from about 0.01 to about 2, such as from about 0.1 to about 1.
[0115] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a free radical thermal initiator that generates free radicals under elevated temperature conditions (e.g., post-heat curing at 300° C. after 3D printing). The addition of the free radical thermal initiator enables multi-mechanism curing in the formulation, namely UV curing and thermal curing. The free radical thermal initiator can be used, for example, to crosslink unreacted vinyl groups that have not yet reacted with thiol groups. The free radical thermal initiator can be used (optionally with a catalyst such as a Pt complex) to react vinyl groups with other available functional groups such as hydrogen or methyl groups, thereby initiating a second type of reaction. If desired, a combination of different types of free radical thermal initiators can be used. Specific examples of free radical thermal initiators include benzoyl peroxide; dicumyl peroxide, 2,2'-azobisisobutyronitrile; carbonylcyclovinylmethylsiloxane platinum complex; divinyltetramethyldisiloxane platinum complex; or combinations or derivatives thereof. When present, the free radical thermal initiator is present in a concentration of from about 0.00001 wt % to about 10 wt % of the UV curable pre-ceramic formulation.
[0116] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a free radical inhibitor. The free radical inhibitor may be included in the formulation to inhibit unwanted polymerization of areas outside the desired printing area so as to achieve sufficient resolution of the desired lattice structure. In a preferred embodiment, the free radical inhibitor is an antioxidant. Specific examples of free radical inhibitors include hydroquinone; methyl hydroquinone; ethyl hydroquinone; methoxy hydroquinone; ethoxy hydroquinone; monomethyl ether hydroquinone; propyl hydroquinone; propoxy hydroquinone; tert-butyl hydroquinone; n-butyl hydroquinone; or a combination or derivative thereof. When present, the free radical inhibitor is present in a concentration from about 0.00001 wt % to about 1 wt % of the UV-curable pre-ceramic formulation.
[0117] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a 3D printing resolution agent. A "3D printing resolution agent" is a compound that improves print quality and resolution by curing the desired area including exposure to laser or light. In certain embodiments, the 3D printing resolution agent works by absorbing light at a desired wavelength (e.g., UV light or visible light) and converting the energy into thermal energy or radiation at a higher wavelength. The use of a 3D printing resolution agent improves print quality and resolution by curing laterally and / or vertically in a print bath including exposure of the laser or light to the desired area. The 3D printing resolution agent can be selected from a UV absorber, a fluorescent agent, an optical brightener, or a combination thereof. Specific examples of 3D printing resolution agents include 2-(2-hydroxyphenyl)-benzotriazole; 2-hydroxyphenyl-benzophenone; 2-hydroxyphenyl-s-triazine; 2,2′-(2,5-thiophenediyl)bis(5-tert-butylbenzoxazole); 2,2′-(1,2-ethylenediyl)bis(4,1-phenylene)bisbenzoxazole; or combinations thereof. When present, the 3D printing resolution agent is present in a concentration of from about 0.00001 wt % to about 10 wt % of the UV-curable pre-ceramic formulation.
[0118] In various embodiments, a UV-curable pre-ceramic formulation for making three-dimensional photonic crystals includes a solid filler. The solid filler can provide various benefits, such as reducing curing and pyrolysis shrinkage, increasing the crack strength of the obtained ceramic, and / or providing seeds for crystallization and assisting crystallization to enhance crystallinity when subjecting amorphous or semi-crystalline ceramic materials to high temperature treatment (e.g., greater than 1200° C.). Preferably, the solid filler is a solid that is stable at the selected pyrolysis temperature (e.g., 750° C. or higher), so that the solid filler does not dissociate, melt, or evaporate during pyrolysis.
[0119] The optional solid phase filler may have a range of compositions, including but not limited to silicon-based ceramics, non-silicon-based ceramics, carbide-based ceramics, nitride-based ceramics, or combinations thereof. Silicon-based ceramics for solid phase fillers include but are not limited to SiOC, SiO2, SiCN, SiC, or SiCBN. Non-silicon-based ceramics for solid phase fillers include but are not limited to alumina, zirconium oxide, titanium dioxide, or other metal oxides. Carbide-based ceramics for solid phase fillers include but are not limited to carbon, diamond, TiC, ZrC, HfC, or other metal carbides. Nitride-based ceramics for solid phase fillers include but are not limited to Si3N4, TiN, ZrN, or other metal nitrides.
[0120] When present, the solid filler is present in a concentration of from about 0.1 vol % to about 70 vol % of the UV-curable pre-ceramic formulation, such as from about 1 vol % to about 50 vol % of the UV-curable pre-ceramic formulation.
[0121] Solid phase filler particles can have an average particle size from about 10 nanometers to about 1000 microns. In order to increase the omnidirectional reflectivity in the final ceramic material, it is preferred that the average particle size of the solid phase filler is about 100 microns or less, about 10 microns or less, or about 1 micron or less. The geometric shape of the solid phase filler can be, for example, spherical particles, fibers, whiskers, nanotubes, nanorods or flat platelets.
[0122] Particle size, rod width and lattice constant can be measured by different techniques, such as including dynamic light scattering, laser diffraction or image analysis. Dynamic light scattering is a non-invasive established technique for measuring the size and size distribution of particles typically in the submicron region (and the latest technology is even 1 nanometer). Laser diffraction is a widely used particle measurement technique for materials ranging in size from hundreds of nanometers to several millimeters. Exemplary dynamic light scattering instruments and laser diffraction instruments for measuring particle size can be obtained from Malvern Instruments Ltd., Worcestershire, UK. Image analysis can be performed directly on micrographs, scanning electron micrographs or other images to estimate particle size and distribution.
[0123] In some embodiments, the solid phase filler effectively inoculates the crystallization of the preferred ceramic phase by allowing the epitaxial growth of the preferred phase in the absence of a nucleation barrier. After the pyrolysis of the pre-ceramic polymer, an amorphous ceramic is generally obtained. In order to increase strength and hardness, and reduce high temperature creep, the amorphous ceramic material can be crystallized or the semi-crystalline material can be further crystallized into a preferred ceramic phase. This can be achieved by high temperature heat treatment, such as at a temperature higher than the pyrolysis temperature, just after pyrolysis or at a later time. Such crystallization can be promoted by providing seeds for crystallization. In a non-limiting manner, the mechanism can include providing a surface for the epitaxial growth of the preferred phase or multiple ceramic phases. For example, the crystallization of β-SiC in amorphous SiC or SiCN ceramics derived from a polycarbosilane-based or polysilazane-based resin can be promoted by small (e.g., 1 nanometer to 5 micrometers) β-SiC crystals. As another example, crystallization of the α-phase or β-phase of Si3N4 in an amorphous Si3N4 or SiCN ceramic derived from a polysilazane-based resin can be promoted by small (e.g., 50 nanometers to 5 micrometers) α-Si3N4 or β-Si3N4 crystals, respectively. Other solid phase fillers can be selected to promote crystallization, where epitaxial growth on one crystal plane with low lattice stress has typical constraints. Crystallization of amorphous or semi-crystalline materials can be carried out at a temperature from about 1200°C to about 2000°C, such as from about 1300°C to about 1600°C. Crystallization can last, for example, from about 1 hour to about 100 hours, depending on the temperature and the material being crystallized.
[0124] The UV-curable pre-ceramic formulations disclosed herein can be 3D printed using many different methods. Preferred methods include stereolithography, two-photon lithography, multi-beam interference lithography, binder jetting, polymer jetting, or a combination thereof.
[0125] Stereolithography is a 3D printing technology for making parts in a layer-by-layer manner using a photochemical process by which light (e.g., UV light) causes monomers and oligomers to polymerize or crosslink together to form polymers. In stereolithography, layers of pre-ceramic resin are cured from the top or bottom using, for example, UV laser rastering, projection microstereolithography, digital light projection, or liquid crystal device projection.
[0126] In two-photon lithography, or in general multiphoton lithography, structuring is done by irradiating a negative or positive photoresist with light of a defined wavelength. Two-photon absorption is exploited to induce a solubility change in the photoresist. This method relies on a multiphoton absorption process in a material that is transparent at the wavelength of the laser used to create the pattern. By scanning and appropriately modulating the laser, polymerization occurs at the focus of the laser and can be controlled to create arbitrary three-dimensional periodic patterns. Multiphoton lithography is useful for creating small lattice features in photosensitive materials without the use of complex optical systems or photomasks.
[0127] In multi-beam interference lithography, an interference pattern of two or more coherent light waves is set and recorded in a photoresist layer. This interference pattern consists of a series of periodic fringes representing intensity minima and maxima. During the lithography process after exposure, a photoresist pattern corresponding to this periodic intensity pattern appears. This method is based on the interference of multiple coherent light beams originating from the diffraction of a large diameter collimated beam on a transmission phase mask. The parameters (period and modulation depth) of the phase mask are selected to produce an interference pattern with high contrast and narrow maxima that are well separated. Multi-beam interference lithography is a technique for forming periodic array patterns of fine lattice features without the use of complex optical systems and photomasks.
[0128] In general, "jetting" of a material means selectively depositing droplets of a build material onto a build bed to create a three-dimensional object. Jetting can be implemented by, for example, liquid deposition, vapor deposition, or liquid-aerosol deposition via spraying (e.g., via a nozzle in communication with the material under pressure), impact (e.g., via a tube or pipe in communication with the pumped material), or other means. In binder jetting, a pre-ceramic resin is jetted into a selected location and cured, such as via UV light or heat. This process is similar to conventional binder jetting methods, but uses a pre-ceramic resin instead of a binder. After the initial step of binder jetting, another layer of pre-ceramic resin can be spread on the 3D printed polymer layer, followed by resin jetting and curing. For larger structures, this process can be repeated many times. In polymer jetting, a liquid pre-ceramic resin is jetted and the desired pattern is written. When the mixture is dispensed, it is exposed to UV light such as a laser, LED, or plasma source and cured into a polymer. Multiple mixtures can be dispensed through different nozzles, allowing more than one type of resin to be used simultaneously. This produces customized mechanical properties of the final ceramic structure (after pyrolysis).
[0129] Typically, but not necessarily, the pre-ceramic formulation is transferred (printed) to the area of interest, such as via stereolithography or multiphoton lithography, followed by polymerization or polymerization occurring simultaneously with printing. Preferably, the photopolymerization and 3D printing sub-steps of step (c) are performed simultaneously at the desired location (e.g., layer) of the part. In some embodiments, the polymerization and 3D printing sub-steps are performed semi-simultaneously, wherein the method is performed multiple times overall, while at each repetition, a certain amount of printing and a certain amount of polymerization occur. In some embodiments, it is also possible to first polymerize the pre-ceramic resin and then 3D print the already prepared polymer - especially when the polymer is a thermoplastic material. In any case, 3D printing and photopolymerization of the pre-ceramic resin produces a pre-ceramic polymer that is spatially arranged in the geometry of the three-dimensional photonic crystal unit cell.
[0130] In some embodiments, curing or converting the pre-ceramic resin formulation to a pre-ceramic polymer includes crosslinking. A crosslink is a bond that connects one polymer chain to another polymer chain. The crosslink bond can be a covalent bond or an ionic bond. When polymer chains are linked together by crosslinking, they lose a portion of their ability to move as individual polymer chains. Crosslinking is a characteristic property of thermosetting plastic materials. In most cases, crosslinking is irreversible unless ionic bonds are used in reversible crosslinking.
[0131] In some embodiments, when converting monomers to polymers, a gel is first formed. After the gel is formed, as the monomer conversion further increases, the chains are cross-linked together to form a solid material. A "gel" is a solid jelly-like material that can have properties ranging from soft and weak to hard and strong. When in a stable state, the gel does not show flow. By weight, gels are mainly liquids, but due to the three-dimensional cross-linked network within the liquid, they also behave like solids. The gel can approximate the geometry of the selected three-dimensional photonic crystal unit cell.
[0132] After 3D printing a part using any of the above methods, or another method, the part can be post-heat cured before pyrolysis to produce a ceramic structure. A post-curing step can be employed, for example, to crosslink unreacted functional groups. Post-curing can be achieved by additional UV exposure and / or thermal post-curing in an oven at an elevated temperature (e.g., 60° C.-500° C.) for about 10 minutes to about 8 hours. When post-heat curing is used, it can be beneficial to include a thermal initiator in the initial pre-ceramic resin to facilitate subsequent thermal curing.
[0133] Direct near-net-shape conversion of pre-ceramic 3D printed polymers to ceramic structures can be achieved by pyrolysis or other thermal treatments such as (but not limited to) sintering, annealing, or calcining. Typically, thermal treatments are based on heating the 3D printed structure under various inert or reactive atmospheres for extended periods of time. The resulting ceramic structure is or includes a three-dimensional photonic crystal.
[0134] Thermal treatment can be carried out for extended periods of time under various atmospheres including, but not limited to, N2, Ar, He, air, CO2, CH4, C2H6, C2H4, NH3, or combinations thereof. The treatment pressure can vary, for example, from about 1 bar to about 20 bar. Vacuum pyrolysis can also be employed, wherein the treatment pressure is less than 1 bar, optionally carried out under various atmospheres including, but not limited to, N2, Ar, He, air, CO2.
[0135] Pyrolysis or other heat treatment may include heating from ambient temperature to an elevated temperature, from about 150°C to about 1500°C, such as from about 500°C to about 1200°C, at a heating rate of 0.1-20°C / min. In some embodiments, a slow heating rate (e.g., less than 10°C / min) may allow volatile gases to escape, thereby minimizing porosity in the final part. When porosity is desired, a higher heating rate (e.g., greater than 20°C / min) may be used.
[0136] Pyrolysis or other thermal treatments may also include dwelling at an elevated temperature (eg, 950° C.) for at least about 1, 10, 30, or 60 minutes, or at least about 1, 2, 3, 4, 5, 6, 7, or 8 hours, or longer.
[0137] After heat treatment, the material may be cooled back to ambient temperature at a cooling rate (on the order of 0.1-20°C / min). In some embodiments, faster cooling (eg, on the order of greater than 20°C / min) is required, for example to freeze the desired microstructure.
[0138] In some embodiments, a first heat treatment is performed at a first temperature, such as from about 150°C to about 1100°C, for example, from about 300°C to about 1000°C, to produce an amorphous or semi-crystalline ceramic material. A second heat treatment is then performed at a second temperature higher than the first temperature, such as from about 1100°C to about 2000°C, for example, from about 1200°C to about 1600°C. As discussed earlier, the second heat treatment can enable the amorphous or semi-crystalline ceramic material to further crystallize into a crystalline ceramic material. The first heat treatment can be performed under an inert or reactive atmosphere, while the second heat treatment is typically performed under an inert atmosphere. The heating rate of both the first heat treatment and the second heat treatment can be from about 0.1-20°C / min. The residence time of both the first heat treatment and the second heat treatment can be, for example, from about 15 minutes to about 5 hours, depending on the size and cross-section of the ceramic structure. A typical residence time is about 1 hour for each of the first heat treatment and the second heat treatment.
[0139] The thermal treatment is preferably performed after polymerization and any (optional) thermal post-curing of the 3D printed pre-ceramic polymer. In certain embodiments, the thermal treatment coincides with polymerization, thermal post-curing, or a combination of both (i.e., in time and / or temperature). It will also be appreciated that even when sequential operation is contemplated, a certain amount of ceramic formation may occur prior to the planned step of the thermal treatment due to the intrinsic kinetics and thermodynamics of the reaction system.
[0140] In some embodiments, a reactive heat treatment is performed, wherein the gas initially present is reactive to the initial polymer, the final ceramic material, or both. When the gas is reactive, it can react with the component and cause it to leave the material. Alternatively or in addition, the gas can react with the component and remain with the base material. It is also possible that the gas reacts and forms products, some of which leave the material and the rest remain with the material. The reactive gas can be selected from O2, O3, air, CO, CO2, H2, H2O, CH4, SO2, H2S, NH3, NO, NO2, N2O, C1-C5 hydrocarbons, etc. In certain embodiments where there is nitrogen content in the final ceramic material (e.g., Si3N4 or SiCN), NH3 is included as a reactive gas together with an inert gas (e.g., Ar) during the heat treatment. When it is desired to reduce the oxygen content in the final ceramic material, heat treatment can be performed with hydrogen or hydrocarbons (e.g., methane, ethane, or propane) together with an inert gas (e.g., Ar). The maximum temperature of the reactive heat treatment can be, for example, about 300°C to about 1500°C. The system pressure can also be adjusted to affect the gas atmosphere.
[0141] Pyrolysis or other heat treatment methods produce three-dimensional photonic crystals, which can contain various ceramic materials, such as but not limited to SiC, SiOC, Si3N4, SiON, SiCN, SiOCN, SiBN, SiBCN, BN, TiO2, ZrO2, ZnO or combinations thereof. The composition of the ceramic 3D photonic crystal depends directly on the composition of the starting pre-ceramic resin. When carbon is desired in the 3D photonic material, the fraction of carbon can be customized, for example, by adding phenyl groups to the side chains of the polymer or by using carbon-based crosslinkers such as divinylbenzene.
[0142] During the heat treatment process, whether an inert or reactive heat treatment technique is used, gases are evolved. During the conversion of the pre-ceramic polymer to a ceramic structure, gases are formed by decomposition reactions of the polymer and other components that may be present (e.g., photoinitiators, free radical inhibitors, and / or 3D printing resolution agents). The evolved gases or vapors may include (but are by no means limited to) CH4, H2, CO, CO2, H2O, SO2, H2S, CH3S, etc.
[0143] The overall mass loss associated with the conversion of a pre-ceramic polymer to a ceramic structure can vary widely, such as from about 1 wt% to about 90 wt%, for example about 5 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, or 80 wt%. The overall mass loss will be determined by the starting formulation (e.g., organic to inorganic fraction) and by the process parameters. In principle, the lost mass can be recovered separately and used for other purposes.
[0144] Pre-ceramic polymers may shrink as they are converted into a ceramic structure. (See e.g. Figure 8 and Fig. 9 ). Linear shrinkage (calculated in a single dimension such as height) can be, for example, from 0% to about 60%. It should be noted that mass loss and shrinkage are not necessarily related. In some embodiments, there is not much (if any) shrinkage with high mass loss. These embodiments tend to produce higher porosity and therefore lower density. In some embodiments with high mass loss, there is significant shrinkage unless solid phase fillers are included. These embodiments tend to produce lower porosity, or no pores, and therefore higher density (e.g., fully dense ceramic materials). Finally, in some embodiments, there is little mass loss, but shrinkage associated with chemical reactions occurs. These embodiments also tend to produce relatively high density.
[0145] Despite the shrinkage (if any), the overall shape (relative geometry) of the 3D printed pre-ceramic polymer can be preserved in the final ceramic structure. That is, when the shrinkage is uniform in all dimensions, the geometric features (lattice parameters) are preserved in the part: it is a reduced form in all three dimensions. In some embodiments, the shrinkage is approximately uniform, which means that the geometric features are substantially maintained, with slight deviations. Fig. 9 This is the case. Uniform shrinkage is possible when there is no random cracking during the conversion of the pre-ceramic polymer to the ceramic structure, and when the reaction and gas evolution are isotropic within the material. It should be noted that very small features, such as at the nanoscale, may not be preserved during an otherwise uniform shrinkage.
[0146] Practically speaking, uniform shrinkage (or no shrinkage) can form parts that are "net shape" or "near net shape". "Net shape" means that geometric features are preserved, so that the manufactured 3D photonic crystal allows final production to match the intended design with little or no post-processing. "Near net shape" means that geometric features are not completely preserved, but only minimal post-processing or manual processing is required. Both net shape and near net shape parts require little or no machining, polishing, bonding, surface finishing, or assembly.
[0147] In some embodiments, the starting pre-ceramic resin is designed to allow ceramic structures to be formed with high thermal stability (e.g., chemical and physical stability at temperatures greater than 1500° C.) and good mechanical strength (including stiffness, flexural strength, hardness, and / or fracture toughness).
[0148] The ceramic structure may be characterized by a theoretical density of at least 50%. "Theoretical density" refers to the actual density of the ceramic structure calculated as a percentage of the theoretical density of the material itself in the absence of pores. For example, from a ceramic structure having a theoretical density of 2.1 g / cm 3 The base material has an inherent (bulk) density of 2.0 g / cm 3 A ceramic structure having an absolute density of 2.0 / 2.1=95% of theoretical density is exhibited. In various embodiments, the ceramic structure is characterized by a theoretical density of about (or at least about) 50%, 60%, 70%, 75%, 80%, 85%, 90%, or 95%. In certain embodiments, without limitation, the ceramic structure is a fully dense structure, which means that the ceramic structure has a theoretical density of at least 99% (e.g., substantially 100%). In g / cm 3 The absolute density in units will vary depending on the choice of base material. Generally speaking (without limitation), a range from about 0.1 g / cm 3 To about 5g / cm 3 The absolute density of a fully dense ceramic may be, for example, from about 1 g / cm 3 About 4g / cm 3 density.
[0149] The strength of the final ceramic material will vary depending on the initial pre-ceramic resin and processing parameters. In some embodiments, the final ceramic material is characterized by a Young's modulus of at least about 200 GPa, 300 GPa, 400 GPa, 500 GPa, or more measured at 25°C. In some embodiments, the final ceramic material is characterized by a flexural strength of at least about 300 GPa, 400 GPa, 500 GPa, or more measured at 25°C. In some embodiments, the final ceramic material is characterized by a hardness of at least about 10 GPa, 20 GPa, 30 GPa, or more measured at 25°C.
[0150] The engineering strength of the ceramic part will also depend on the lattice geometry. It should be noted, for example, that silicon oxycarbide microlattices made using the method of the present invention exhibit higher strength than ceramic foams of similar density.
[0151] The thermal stability of the final ceramic material will vary primarily depending on the initial pre-ceramic resin. In various embodiments, the final ceramic material is thermally stable when exposed to a temperature of 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or 1600°C for 24 hours in an air atmosphere at 1 bar pressure. Thermal stability at least means that the ceramic material does not melt at these temperatures, and it is also preferred that the ceramic material does not react (e.g., by oxidation or reduction), undergo thermal shock, or physically decompose (introduce defects) at these temperatures.
[0152] Examples
[0153] Example 1: UV-curable carbosilane resin was 3D printed and then pyrolyzed and crystallized into SiC.
[0154] In this Example 1, a commercial carbosilane material was obtained according to the present specification and functionalized to make it UV curable. A flat disk of the functionalized carbosilane was polymerized via UV curing to produce a flat disk of polycarbosilicic acid polymer.
[0155] The flat disk of polycarbosilicic acid polymer was pyrolyzed at 1000°C for 1 hour in an argon atmosphere. The polycarbosilane polymer was then crystallized at 1400°C for 4 hours in an argon atmosphere to produce a polycrystalline SiC ceramic disk (this SiC material contained less than 10 wt% oxygen).
[0156] Reflectivity measurements were performed in a variable-angle spectroscopic ellipsometer. Figure 7 The optical constants measured by ellipsometry are shown. Figure 7 In Figure 1, the real (n) and imaginary (k) refractive indices are shown for a 3D printed carbosilane resin after heat treatment (n = dashed line, k = solid line). The measured n and k refractive indices show characteristic photopolariton resonances close to 11 μm, as expected from SiC with low oxygen content. The real refractive index is greater than 2 in the MWIR region and greater than 3 at wavelengths longer than 14 μm, indicating that this ceramic material is capable of achieving a full bandgap when fabricated with a suitable lattice unit cell.
[0157] Example 2: UV-curable carbosilane resin was 3D printed and subsequently pyrolyzed and crystallized into SiOC.
[0158] In this Example 2, a commercial carbosilane material was obtained according to the present specification and functionalized to make it UV curable. A two-photon lithography tool (Nanoscribe GmbH, Karlsruhe, Germany) 3D printed the starting functionalized carbosilane resin into woodpile-shaped polycarbosilane polymer structures. Figure 8 is a SEM image showing a 4 unit cell thick 3D printed wood pile structure (scale bar = 30 μm).
[0159] The woodpile-shaped polycarbosilane polymer structure was then pyrolyzed at 1000°C for 1 hour, at which point the structure converted to a ceramic material and shrunk in volume by nearly 30%. Fig. 9 is a SEM image (scale bar = 30 μm) of a woodpile-shaped SiOC ceramic material (such SiOC material contains more than 30 wt% oxygen). It is observed that there are multiple layers stacked on top of each other, such as in Figure 5AThere are four layers in this wood pile structure.
[0160] Fig.10 is a high magnification SEM image of a SiOC woodpile structure (scale bar = 5 μm), showing a column width of about 0.5 μm and a column-column spacing of about 3 μm. The structural nodes are present with an effective diameter of about 1-1.5 μm, which is at least twice the column (rod) width. The structural node material is also SiOC derived from the pyrolysis of polycarbosilane.
[0161] In various embodiments, the structures disclosed herein can be used as omnidirectional reflectors, thermal emitters, or semiconductor laser coolers with tunable wavelengths. Additional applications of interest include, for example, thermal insulation coatings, thermophotovoltaic devices, propulsion structures (blades, impellers, nacelles, and propellers), control surfaces (fins and leading edges), hypersonic structures (thermal protection systems and heat shields), high wear parts (brakes, clutches, and rotors), catalyst carrier structures, pump components, filters, brakes, and clutches. Certain embodiments can achieve blackbody emission feature control. Thermal stability in extreme environments can achieve customized thermal emission spectra for feature control. In various embodiments, the IR reflector provided herein can reflect peak blackbody radiation with a wavelength of 2-3 μm, for example, reflecting at least 10%, 20%, 30%, 40%, or 50% of the radiated power.
[0162] In this detailed description, reference has been made to a number of embodiments and drawings in which specific exemplary embodiments of the invention are shown by way of illustration. These embodiments are described in sufficient detail to enable those skilled in the art to practice the invention, and it should be understood that those skilled in the art may make modifications to the various embodiments disclosed.
[0163] When the above method and steps indicate that certain events occur in a certain order, those of ordinary skill in the art will recognize that the order of certain steps can be modified, and such modification is carried out according to variants of the present invention. In addition, certain steps can be carried out simultaneously by parallel processes when possible, or can be carried out successively.
[0164] The above-described embodiments, variations, and figures should provide an indication of the utility and versatility of the present invention. Other embodiments that do not provide all of the features and advantages set forth herein may also be used without departing from the spirit of the present invention.
[0165] All publications, patents, and patent applications cited in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually set forth herein.
Claims
1. An omnidirectional infrared reflector, comprising a three-dimensional photonic crystal, wherein the three-dimensional photonic crystal contains: rods of a first material having a first refractive index, wherein the rods are arranged to form a plurality of lattice periods, the plurality of lattice periods being identical in all three dimensions, wherein the rods are connected at a plurality of structural connection nodes, wherein the structural connection nodes mechanically reinforce the rods, wherein the lattice period is characterized by a lattice spacing, and wherein the rods are characterized by a rod radius or width; and a second material having a second refractive index lower than the first refractive index, wherein the rods are embedded in the second material, wherein the lattice spacing and the rod radius or width are selected to produce a photonic band gap within a selected band of the infrared spectrum, and The three-dimensional photonic crystal has a rhombus unit cell.
2. An omnidirectional infrared reflector according to claim 1, wherein the selected band of the infrared spectrum is from 1 μm to 15 μm wavelength.
3. An omnidirectional infrared reflector according to claim 2, wherein the selected band of the infrared spectrum is from 2 μm to 3 μm wavelength.
4. The omnidirectional infrared reflector of claim 1, wherein the photonic bandgap is a complete photonic bandgap within the selected band of the infrared spectrum. The omnidirectional infrared reflector according to claim 1 , wherein the lattice pitch is from 0.5 μm to 20 μm. The omnidirectional infrared reflector according to claim 5 , wherein the lattice pitch is from 1 μm to 3 μm.
7. The omnidirectional infrared reflector according to claim 1, wherein the rod radius or width is from 50 nm to 5 μm.
8. The omnidirectional infrared reflector according to claim 1, wherein the ratio of the rod radius or width to the lattice spacing is from 0.05 to 0.
50.
9. The omnidirectional infrared reflector of claim 1, wherein the plurality of lattice periods is at least 4 lattice periods that are periodic in all three dimensions.
10. The omnidirectional infrared reflector of claim 1, wherein the first refractive index is at least 2, and wherein the second refractive index is less than the first refractive index. The omnidirectional infrared reflector according to claim 1 , wherein the first material is a ceramic material.
12. The omnidirectional infrared reflector according to claim 11, wherein the ceramic material is selected from the group consisting of SiC, SiOC, Si3N4, SiCN, TiO2, ZrO2 and combinations thereof.
13. The omnidirectional infrared reflector of claim 11, wherein the ceramic material is a pyrolyzed form of a pre-ceramic resin, the pre-ceramic resin being optionally a 3D printed pre-ceramic resin.
14. The omnidirectional infrared reflector according to claim 1, wherein the second material is selected from the group consisting of MgF2, LiF, CaF2, BaF2, SiO2, SiOC, and combinations thereof.
15. The omnidirectional infrared reflector of claim 1, wherein the structural connection nodes each have a structural node radius or width that is at least 10% greater than the rod radius or width.
16. The omnidirectional infrared reflector of claim 1, wherein the omnidirectional infrared reflector is thermally stable when exposed to a temperature of 1300°C for 24 hours in an air atmosphere at a pressure of 1 bar.
17. The omnidirectional infrared reflector of claim 1, wherein the omnidirectional infrared reflector comprises a plurality of layers, each layer having a different three-dimensional photonic crystal.
Citation Information
Patent Citations
Monomer formulations and methods for 3D printing of preceramic polymers
US20180148380A1
Ordered cellular structures and methods of manufacturing the same
US10399909B1
Three-dimensional photonic crystal and optical element
US20060029349A1